Penerapan Asuhan Kefarmasian dan Media Sosial dalam Meningkatkan Pendapatan Apotek - Alwiyah Mukaddas; M Sulaiman Zubair; Yusriadi Yusriadi (Universitas Mathla'ul Anwar Banten, 2020)
IMPLEMENTATION OF PHARMACEUTICAL CARE AND SOCIAL MEDIA MARKETING IN IMPROVING THE PHARMACY OMZET. A pharmacy is a place for pharmaceutical practice of pharmacists. Apotek Pendidikan Tadulako has three functions, which are education, social and business/profit functions. The purpose of this activity is to improve the pharmaceutical care, inventory management aspects, and marketing that affect to the increasing of pharmacy omzet. The solutions offered include the adding of a variety of non-drug supplies in the form of vaccines and home care medical devices, strengthening of pharmacists role in providing plenary services in the form of CIE (Consultation, Information, Education), establishing the cooperation with other health institutions, and implementing the social media marketing (SMM) ) includes Facebook, Instagram, Twitter and YouTube. The results of these activities have an impact on increasing the omzet of pharmacy every month. The follow-up plan is the application of an integrated Management Information System (SIM) and the application of internet-based marketing techniques with a website that is an online pharmacy.